2017
DOI: 10.1177/1687814017692515
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition analysis in a sphere of combustible materials

Abstract: In this article, we look at spontaneous combustion due to exothermic chemical reaction taking place within a stockpile of combustible material. The model includes mass and energy balance equations in a spherical domain. The complicated chemical reaction is simplified by considering a one-dimensional process. The differential equations governing the problem are solved using semi-implicit finite difference method. The effects of kinetic parameters embedded within the system are analyzed and the results are expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 13 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…We employ consistent, efficient, accurate, and robust semi-implicit finite difference algorithms for the solution process of the governing equations, see for example [23,24,25,26,28,27] for details. Taking 0 ≤ ξ ≤ 1, the implicit terms, for our semi-implicit algorithms, correspond to the intermediate time level (N + ξ).…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…We employ consistent, efficient, accurate, and robust semi-implicit finite difference algorithms for the solution process of the governing equations, see for example [23,24,25,26,28,27] for details. Taking 0 ≤ ξ ≤ 1, the implicit terms, for our semi-implicit algorithms, correspond to the intermediate time level (N + ξ).…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…Some mathematical models that are less expensive and faster than experimental approaches have been implemented in the literature to explain the auto-ignition of combustible materials in a stockpile. For instance, a one-step combustion process of heat transfer in a spherical channel was investigated in [12,13]. According to their reports, the system maintains stability as heat escapes into the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the reviewed literature in [12][13][14]22,28], this study focuses on an investigation of the thermal decomposition of Carreau fluid in a rectangular stockpile with variable thermophysical properties. It is believed that this present study has not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The combustion process is so complicated and results with nonlinear molecular interactions [8][9], hence the ODE governing the problem is nonlinear and can only be solved by numerical methods, and in this case, the RKF45 coupled with the Shooting technique is employed [10][11]. Many studies on heat transfer analysis were carried out in a rectangular slab [12][13], cylindrical pipe [14][15], and spherical domain [16]. In the investigations done already, a one-step complete combustion process represented by the following equation was considered:…”
Section: Introductionmentioning
confidence: 99%